Ionotropic glutamate receptors activate cell signaling in response to glutamate in Schwann cells. Issue 4 (10th January 2017) - Campana, Wendy M.; Mantuano, Elisabetta; Azmoon, Pardis; Henry, Kenneth; Banki, Michael A.; Kim, John H.; Pizzo, Donald P.; Gonias, Steven L.
Abstract : In the peripheral nervous system, Schwann cells (SCs) demonstrate surveillance activity, detecting injury and undergoing trans ‐differentiation to support repair. SC receptors that detect peripheral nervous system injury remain incompletely understood. We used RT‐PCR to profile ionotropic glutamate receptor expression in cultured SCs. We identified subunits required for assembly of N ‐methyl‐D‐aspartic acid (NMDA) receptors (NMDA‐Rs), α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptors, and kainate receptors. Treatment of SCs with 40–100 μM glutamate or with 0.5–1.0 μM NMDA robustly activated Akt and ERK1/2. The response was transient and bimodal; glutamate concentrations that exceeded 250 μM failed to activate cell signaling. Phosphoprotein profiling identified diverse phosphorylated proteins in glutamate‐treated SCs in addition to ERK1/2 and Akt, including p70 S6‐kinase, glycogen synthase kinase‐3, ribosomal S6 kinase, c‐Jun, and cAMP response element binding protein. Activation of SC signaling by glutamate was blocked by EGTA and dizocilpine and by silencing expression of the NMDA‐R NR1 subunit. Phosphoinositide 3‐kinase/PI3K functioned as an essential upstream activator of Akt and ERK1/2 in glutamate‐treated SCs. When glutamate or NMDA was injected directly into crush‐injured rat sciatic nerves, ERK1/2 phosphorylation was observed in myelinated and nonmyelinating SCs. Glutamate promoted SC migration by a pathway that required PI3K and ERK1/2. These results identified ionotropic glutamate receptors and NMDA‐Rs, specifically, as potentially important cell signaling receptors in SCs. —Campana, W. M., Mantuano, E., Azmoon, P., Henry, K., Banki, M. A., Kim, J. H., Pizzo, D. P., Gonias, S. L. Ionotropic glutamate receptors activate cell signaling in response to glutamate in Schwann cells. FASEB J . 31, 1744–1755 (2017) www.fasebj.org